The Impact of International Stock Market Indices on Indonesia's Composite Index Based on Data from 2015 to 2024 - Heri Sasono; Ahmad Syukri; Pudjo Irianto (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
Global stock markets are increasingly interconnected, influencing emerging markets such as the Indonesia Composite Index. This study aims to analyze the collective and individual impacts of the Nikkei, New York Stock Exchange, FTSE, and ASX indices on the Jakarta Composite Index from 2015 to 2024. This study uses a quantitative approach to ensure a robust analysis and uses multiple linear regression analysis. Data collected from the annual closing values ​​of the Indonesia Stock Exchange, Tokyo Stock Exchange, New York Stock Exchange, London Stock Exchange, and Australia Stock Exchange, processed with the Statistical Package for Social Sciences version 26. The results show that global indices collectively influence the Jakarta Composite Index, explaining 85.3% of its variance. Individually, only the New York Stock Exchange has a significant positive effect, while the Nikkei, FTSE, and ASX indices do not show significant individual impacts. The study concludes that investors and policymakers should monitor the dynamics of the United States market to anticipate the movement of the Jakarta Composite Index, while future research should explore additional factors such as exchange rates to improve the understanding of the dynamics of the Indonesian market.